2017
DOI: 10.17576/jkmjc-2017-3303-13
|View full text |Cite
|
Sign up to set email alerts
|

Examining Malaysian Leader Characteristics in a Manager-Subordinate Relationship

Abstract: The paper discusses the findings of the first stage of data collection from a study on the characteristics of leaders in manager-subordinate relationship in Malaysian organizations. The findings are based on in-depth interviews conducted with focus groups involving Malaysian employees, which focused on employee perspectives on key qualities that leaders possess to uphold and maintain superior-subordinate relationship. The adoption of qualitative approach in this phase of data collection process is crucial in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…The association between PK and media consumption also is found in online platforms (Lee & Xenos, 2019) which suggests the feasibility of this relationship on the social channels. However, as posited by Bode and Dalrymple (2016), information from social media does come from the users of the same social media platforms rather than the journalists thereby leading to the question on the credibility of the information source (Bode & Vraga, 2015;Halim & Azizan, 2017;Mohamad et al, 2016;Shin et al, 2018). For example, the information appeared on Facebook time line usually traced to one of the users on the friend list.…”
Section: Social Media Usagementioning
confidence: 99%
“…The association between PK and media consumption also is found in online platforms (Lee & Xenos, 2019) which suggests the feasibility of this relationship on the social channels. However, as posited by Bode and Dalrymple (2016), information from social media does come from the users of the same social media platforms rather than the journalists thereby leading to the question on the credibility of the information source (Bode & Vraga, 2015;Halim & Azizan, 2017;Mohamad et al, 2016;Shin et al, 2018). For example, the information appeared on Facebook time line usually traced to one of the users on the friend list.…”
Section: Social Media Usagementioning
confidence: 99%
“…A study by Halim and Azizan (2017) have suggested that supervisors who solicit their subordinates' suggestions, are interested in them as people, can casually relate to them, and encourage employees to give ideas when making decisions have a better likelihood of increasing the commitment of subordinates to their work group. A relationship between superior and subordinate that is robust and in harmony will amplify the effectiveness of the team, which in turn will pave the way to reach the goals of the team and general success (Chiniara & Bentein, 2018;Jha, 2017).…”
Section: Team Effectivenessmentioning
confidence: 99%
“…Migrant workers' parents and caregivers should carry out democratic parenting, namely providing a warm attitude, psychological support, and training children to behave constructively. Appreciation given to interpersonal relationships will be more likely to be seen and oriented toward relationships positively (Halim & Azizan, 2017). Thus, parents can encourage children to behave in an adult, responsible, independent manner and act according to their development.…”
Section: Parenting Culture Establishedmentioning
confidence: 99%